The Effect of Fasting Sunnah Mondays and Thursdays on Body Composition, Blood Pressure, and Blood Glucose Levels - Bebasari, Eka; Sofian, Amru; Pratama, Bayu Fajar (Buletin Farmatera, 2021)
Fasting is a form of non-pharmacological intervention to improve health. One of the sunnah fastings that is often done is fasting Monday and Thursday. There is still little research on the benefits of this sunnah fasting. This study is a quasi-experimental study to determine the effect of sunnah fasting on Mondays and Thursdays on body composition, blood pressure, and blood glucose levels. The research subjects were 19 Riau University students who were willing to fast every Monday and Thursday for 4 consecutive weeks (8 days of fasting), were healthy, and did not smoke. Measurement of research parameters was carried out before and after fasting. The results of this study showed differences in the average values of body composition (weight, body mass index, upper arm circumference, waist circumference, waist-hip ratio), systolic blood pressure, diastolic blood pressure, and blood glucose levels before and after fasting. The results of statistical analysis with paired t-test there were significant differences in the average values of upper arm circumference, waist circumference, diastolic blood pressure, and blood glucose levels before and after fasting (p 0.05), but there was no significant difference in body weight, index body mass, waist-to-hip ratio, and systolic blood pressure before and after fasting (p 0.05). There is an effect of Monday and Thursday sunnah fasting on upper arm circumference, waist circumference, diastolic blood pressure, and blood glucose levels.